EVOLUTION OF ARCHITECTURAL SKETCHING FROM HAND GRAPHICS TO DIGITAL MEDIA - Sobko, Yulia; Ovsiіenko Olga; Rіezanova Kateryna (SWorld-Ger Conference proceedings, 2025)
The paper examines the evolution of architectural sketching from traditional hand-drawn graphics to modern digital media. Key stages of development are analyzed, including the impact of technological innovations on the sketching process, its functionality